Developing interventions to improve parental and carer performance of temperature measurement, fever care and knowledge of feverish illness in children - Hernandez-Rodriguez, JP (2014)
Background: Fever is often the initial feature of infectious diseases, which remains a major cause of morbidity and an important cause of mortality in children in the UK, and is one of the most common reasons for children to be taken to a general practitioner. Febrile illness therefore places a considerable burden on children, their families and health care services. The initial disease identification and diagnostic challenge starts at home, with parents and carers differentiating children with suspected serious illness from the vast majority who have self-limiting or minor infections. This thesis aims to understand caregivers’ knowledge, beliefs and actions in the existence of a fever in comparison with NICE guideline advice, and suggests some recommendations to improve their knowledge and management of fever. Method: Four studies were conducted for this thesis. First, a systematic review of 47 studies, including 20,427 participants, was used to understand parents’ knowledge regarding interpretation of temperature measurements, actions to manage a fever, and their beliefs. Second, two focus group interviews in primary care, with 9 parents, were used to explore parental views and beliefs on the management of fever and temperature measurement. Third, a thermometer survey, with 123 thermometers, was used to assess the consistency of advice from information contained in commercially available thermometers, with respect to evidence-based guidelines for feverish illness in children. Fourth, a questionnaire survey, in primary care, with 309 participants, was used to find out carer knowledge of temperature measurement and fever management in children 5 years or younger. Results: Carer knowledge about normal body temperature and fever in children was poor: mild fever was misclassified by many as high. Understanding of what actually constitutes fever ranged widely; carers actively reduced mild fever with antipyretics, used non-recommended methods, and most learned to use a thermometer from its instructions. Most parents did not know what a fever was and believed that it was a harmful condition that may be linked to a more serious disease. Parents wanted to be provided with specific and practical information on the identification of fever and its management. Most of the thermometer information did not include guidance on fever management or thermometer use, did not take into account parental and carer interpretation of fever and disease, however, incorporated unnecessary referrals into health services. Thermometer cost had no influence on the quality of the information provided. Conclusions: The research presented in this thesis suggests that caregivers often lack basic knowledge on temperature measurement and fever care. The study proposes that a simple NICE guideline based educational intervention may help them to correctly take a temperature measurement while assessing other signs of illness, and allow them to provide appropriate management methods at home, and more importantly, seek further referral where necessary. This may help towards decreasing unnecessary attendances in primary and secondary care.